Exploring causal association between malnutrition, nutrients intake and inflammatory bowel disease: a Mendelian randomization analysis - Wang, Shi; Wang, Jing; Meng, Xinyao; Yang, Shimin; Wu, Luyao; Chen, Ke; Li, Zejian; Xiao, Jun; Yu, Xiaosi; Chen, Xuyong; Feng, Jiexiong; Gong, Rui (Frontiers in Nutrition, 2024)
Background Malnutrition has emerged as main side effects of inflammatory bowel disease (IBD) which might also affect the prognosis of IBD. However, whether these associations are causal remains unclear. We aimed to identify the causality of IBD on malnutrition and explore the causal relationship of malnutrition and nutrients intake on IBD by using Mendelian randomization (MR). Methods Single nucleotide polymorphisms associated with IBD, malnutrition and nutrients intake were obtained from previous researches of genome-wide association studies (GWAS) (p < 0.00000005). MR analysis was conducted to evaluate the causality with different methods based on OR and their 95% CIs. Meanwhile, heterogeneity, pleiotropy and MR-PRESSO were used for instrumental variables evaluation. Results The results of MR analysis revealed that IBD, both Crohn disease (CD) and ulcerative colitis (UC), could directly impact the incidence of malnutrition (p-value <0.01). CD is directly related to nutrients such as sugar, fat, VA, VC, VD and zinc, while UC is correlated with carbohydrate, fat, VB12, VC, VD, VE, iron, zinc and magnesium. However, our results suggested that malnutrition could not affect the risk of IBD directly (p > 0.05). Further analysis showed similar results that nutrients intake had no direct effect on IBD, neither CD or UC. Conclusion Our results indicated that IBD increases the risk of malnutrition, however, malnutrition and nutrients intake might not directly affect the progression of IBD.